2006
DOI: 10.1182/blood-2006-02-003988
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol inhibits proliferation, induces apoptosis, and overcomes chemoresistance through down-regulation of STAT3 and nuclear factor-κB–regulated antiapoptotic and cell survival gene products in human multiple myeloma cells

Abstract: IntroductionMultiple myeloma (MM) or plasma cell myeloma is characterized by latent accumulation of secretory plasma cells with a low proliferative index and an extended life span in the bone marrow. 1 The second most prevalent hematologic cancer after non-Hodgkin lymphoma, multiple myeloma accounts for 10% of all hematologic cancers and approximately 2% of all cancer deaths. Conventional therapy for multiple myeloma involves combinations of vincristine, carmustine (bischloroethylnitrosourea), melphalan, cyclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
285
0
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 372 publications
(308 citation statements)
references
References 51 publications
16
285
0
7
Order By: Relevance
“…1 and 3). However, RSV has many additional targets within the cell, including general modulators of transcription Sirtuins (class III histon deacetylases) [48,49], transcription factors NF-κB and STAT3 [16,17] and many enzymes of general cell metabolism [46]. RSV treatment of several melanoma lines induced a relatively modest decrease in the high basal NF-κB activity and NF-κB-dependent transcription in these cells, while downregulation of STAT3 levels and STAT3-dependent transcription was more pronounced (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 and 3). However, RSV has many additional targets within the cell, including general modulators of transcription Sirtuins (class III histon deacetylases) [48,49], transcription factors NF-κB and STAT3 [16,17] and many enzymes of general cell metabolism [46]. RSV treatment of several melanoma lines induced a relatively modest decrease in the high basal NF-κB activity and NF-κB-dependent transcription in these cells, while downregulation of STAT3 levels and STAT3-dependent transcription was more pronounced (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from protein synthesis inhibitors, RSV was previously implicated in sensitization to TRAIL-mediated apoptosis in different cancer cell lines [16,17,35]. Based on its effects on signaling pathways and expression of anti-apoptotic proteins (Fig.…”
Section: Cell Death In Human Melanomas Induced By Either Recombinant mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the efficacy of chemotherapeutics is severely limited because of chemoresistance. Several studies have suggested that the serine-threonine kinase Akt and the transcription factor NF-κB, are the key molecules for protecting cells from undergoing apoptosis, and that the Akt and NF-κB mediated survival signaling pathway is associated with chemoresistance of human tumors (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%
“…PIP2 and PIP3 bind to the PH domain of Akt, resulting in translocation of Akt to the plasma membrane area (4,5). Akt has been reported to be a signal transduction protein that figures prominently in the mechanisms of carcinogenesis and chemoresistance (3,6,7).…”
Section: Introductionmentioning
confidence: 99%